INFORMATION MANAGEMENT IN AN SME - Ruiz L., Edgar (2003)
This article presents a proposal for developing an Enterprise Information System's Architecture that could be useful in a Small and Micro-Enterprise (Pyme) Information Management, considering a case such of LICON S.A., a peruvian enterprise.